Foundational Science Instruction for Clerkship-Phase Medical Students through Integrated Clinical Experience in Transplantation, Transplant Infectious Diseases, and Immunodeficiency. (4th October 2017) - Dulek, Daniel
Abstract: Background: Foundational science instruction is frequently provided during the preclinical phase of undergraduate medical education. Two of the eight key competencies from the 2009 AAMC-HHMI Report on Scientific Foundations for Future Physicians address the application of microorganism biology and cellular/molecular host defense in mechanisms of health and disease. Given the emphasis in these competencies on application of foundational science in the clinical context, significant benefit to the learner may be achieved by providing foundational infectious diseases and immunology teaching in the cerkship phase of undergraduate medical education. The practice of transplant and immunocompromised host (ICH) infectious disease medicine offers an opportunity in which to apply these foundational topics. Methods: 'Immunity and Infections in the Immune-compromised Host', an Integrated Science course (ISC) situated within the third and fourthyear Immersion Phase of the Vanderbilt School of Medicine (VUSM) Curriculum 2.0 was offered 6 times total during the 2015–2015 and 2016–2017 academic years. During each course, didactic and small-group instruction was integrated with four week-long clinical rotations in infectious disease, transplant, or immunology-related subspecialty settings. Results: Thirty-two students participated across the six course offerings. Standardized post-course feedback was provided by 81.2% of students. Of the students providing course review, 92.3% were satisfied or very satisfied with the quality of the course content and 100% were satisfied or very satisfied with the clinical relevance of the course content. One-hundred percent of the students agreed or strongly agreed that the course was well-integrated with other elements of the curriculum, motivated them to continue learning in this area, and supported their learning. Conclusion: Clerkship-phase instruction in foundational infectious diseases and immunology integrated with clinical experience that applies these foundational concepts is well-received by third and fourth year medical students. Infectious disease physicians are uniquely situated to provide key instruction in the foundational sciences. Disclosures: All authors: No reported disclosures.